Amžinojo sugrįžimo mitas, arba laukimas sekuliarioje visuomenėje = The Myth of the Eternal Return, Or Waiting in Secular Society - Vidauskytė, Lina (Religija ir kultūra, 2014)
Walter Benjamin, in his fundamental work The Arcades Project, distinguished three types of relationships with time: the gambler (to pass time, to kill time, expel it; time spills from his every pore); the flâneur (to store the time as battery stores energy) and the third type: he who waits. "He takes in the time and renders it up in altered form - that of expectation." When describing the third type, Benjamin is mainly talking about Auguste Blanqui, French socialist and political activist, who had spent most of his life in prison. In his text L’Eternité par les astres, written while imprisoned in Fort du Taureau, first appears the myth of the eternal return. Later, philosopher Friedrich Nietzsche also discovers this melancholic myth ("the eternal return of the same events"). Both the myth of the eternal return and the belief in progress is the return of the mythical consciousness, as Benjamin claims. Mythical because it does not reflect and does not have an experience. So, it is a modern consciousness without experience, will and time. Does the same repetition mean an empty waiting? Does it mean a nihilistic consciousness and nihilistic waiting? There is no doubt that the third type of relationship with time marks the secular society, or, as Benjamin writes, post-auratic. Aura is the manifestation of the sacred and authenticity. In this article, the modern mythic consciousness is analysed through the concept of a myth by Hans Blumenberg. According to it, the myth is not a form of cognition but rather a way to overcome the "absolutism of reality." This article attempts to show that the third figure - "he who waits" - can be seen as Nietzsche’s "Superman" - the modern world nihilistic figure that correlates to the reality of "eternal return".